2007
DOI: 10.1021/jf071896v
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sampling of Tomato Fruit for Carotenoid Content with Application To Assessing the Impact of Ripening Disorders

Abstract: Color defines one aspect of quality for tomato and tomato products. Carotenoid pigments are responsible for the red and orange colors of tomato fruit, and thus color is also of dietary interest. The aims of this study were (1) to determine the relative importance of field sampling and analytical replication when measuring lycopene and beta-carotene in tomato fruit and (2) to determine the effect of yellow shoulder disorder (YSD) on the content of lycopene and beta-carotene in tomato juice and tissue. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The majority of investigations addresses to an optimum sampling procedure, for example. How many sentinel lymph nodes should be investigated in relation to the stage of breast cancer [ 29 , 31 ], or "optimizing sampling of tomato fruit for carotenoid content, or how to perform endometrial sampling in patients with trophoblastic disease after suction curettage [ 39 , 40 ]. In the early days of stereology several authors took attention on the sampling procedures, as the results of counting interceptions are closely associated to the nature of the used sampling method [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of investigations addresses to an optimum sampling procedure, for example. How many sentinel lymph nodes should be investigated in relation to the stage of breast cancer [ 29 , 31 ], or "optimizing sampling of tomato fruit for carotenoid content, or how to perform endometrial sampling in patients with trophoblastic disease after suction curettage [ 39 , 40 ]. In the early days of stereology several authors took attention on the sampling procedures, as the results of counting interceptions are closely associated to the nature of the used sampling method [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the relative importance of field sampling and analytical replication on carotenoid variance in tomato fruit, Darrigues et al (2008) observed that between-plot field variation was most significant, accounting for 50% and 52% of the total variation for lycopene and b-carotene, respectively. The corresponding contributions of within-plot variation were 7% and 3%, and of uncontrolled error 43% and 45%.…”
Section: Critical Points and Sources Of Errorsmentioning
confidence: 99%
“…To improve the output of high-quality product, some processors structure contracts such that growers receive premiums for fruit based on color and color uniformity. Discoloration due to YSD also reduces lycopene and beta-carotene concentrations in tissue affected by YSD (Darrigues et al, 2008). A reduction in the incidence of YSD could benefit producers, processors, and consumers.…”
mentioning
confidence: 99%